Assessment of botanical composition, biomass yield, nutritional quality and methane production of forages in selected grasslands, southern highlands of Ethiopia - Mosisa, A.; Nurfeta, A.; Bezabih, Melkamu; Tolera, Adugna; Mengistu, S.; Yigrem, S.; Hassen, A. (Elsevier, 2021)
A study was conducted to assess botanical composition, biomass yield, nutritive value and methane production of forages in the grasslands of Kofele district in West Arsi Zone of Oromia National Regional State, southern Ethiopia. Three patches of the grassland including protected grassland, private grazing land used by smallholder farmers and ranch were selected for the study to represent three different grazing land management practices. Quadrats of 0.5 m × 0.5 m were used to determine biomass yield and collect samples of herbaceous forages from each site (12 quadrats from each site). For woody species four 10 m × 10 m plots were established along transect of 200 m with 20 m distance between plots to identify available species (in the ranch only). A total of 20 herbaceous species were identified, out of which 45% were grasses, 15% legumes, 10% sedges and 30% forbs. Out of 17 browse species identified in the ranch, 47.1% were trees while 52.9% were shrubs. The total biomass production from protected grassland (4.34 t/ha) was higher (P<0.05) than that of private grazing land (3.66 t/ha) and ranch (3.76 t/ha). Biomass production of sedge and forbs were the highest (P<0.05) in ranch. The ranges of chemical constituents for grasses were 8.44–10.74%, 52.8–72%, 27.7–37.4%, 3.1–5.6%, 58.2–76% for crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL) and in vitro dry matter digestibility (IVDMD), respectively. The CP and IVDMD for legumes varied from 15.64–20.33% and 80.1–85–1%, respectively. For browses the ranges of CP and IVDMD were 15.41–27.19% and 57.4–81.9%, respectively.. Among grass species, Eragrostis botryodes generated less methane. In general, legumes (5.5–6.5 mL/200 mg) and sedge (6 mL/200 mg) produced less amount of methane compared with grasses (7–10.5 mL/200 mg). Browses (9.5–13.5 mL/200 mg) produced more methane compared with herbaceous species (5.5–10.5 mL/200 mg). In conclusion protecting grassland and using cut and carry feeding system promoted more herbage production. The CP content of grass is generally good but supplementation with legumes and browses are required in practical feeding. The use of legumes with grasses and other browse species is recommended as a feeding strategy to reduce methane production However; further investigations on animal response trials are suggested to see the potential of these feed resources.